2020
DOI: 10.1111/apt.15753
|View full text |Cite
|
Sign up to set email alerts
|

Do the circulating Pre‐S/S quasispecies influence hepatitis B virus surface antigen levels in the HBeAg negative phase of HBV infection?

Abstract: Background: Virus, host factors and their interplay influence Hepatitis B surfaceAntigen serum levels during Hepatitis B Virus (HBV) infection course and treatment. Aim:To study the Pre-S/S circulating quasispecies in a cohort of untreated, HBeAg negative, genotype-D, HBsAg carriers. Methods:We studied 260 carriers: 71 with HBeAg negative infection (ENI; HBV-DNA ≤2000 IU/mL); 42 Grey Zone (GZ; HBV-DNA ≤20 000 IU/mL); 82 chronic hepatitis (CH) and 65 cirrhosis (CI) (HBV-DNA > 20 000 IU/mL). Population sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Sueki et al also reported the presence of amino acid substitutions in HBV pre-S1 and pre-S2, may be related to the emergence of lamivudine resistance during chronic HBV infection [28]. In HBeAg-negative and HBV GT-D carriers, pre-S/S heterogeneity increases with severity of liver disease [29]. Next generation sequencing-based platform may provide an improvement of the clinical application of pre-S mutants in serving as predictive and prognostic markers for HBV-related HCC [30].…”
Section: Discussionmentioning
confidence: 97%
“…Sueki et al also reported the presence of amino acid substitutions in HBV pre-S1 and pre-S2, may be related to the emergence of lamivudine resistance during chronic HBV infection [28]. In HBeAg-negative and HBV GT-D carriers, pre-S/S heterogeneity increases with severity of liver disease [29]. Next generation sequencing-based platform may provide an improvement of the clinical application of pre-S mutants in serving as predictive and prognostic markers for HBV-related HCC [30].…”
Section: Discussionmentioning
confidence: 97%
“…5,6 Previous studies have suggested that preS/S mutations are associated with lower or higher HBsAg levels. 5,7 In this issue of AP&T, Brunetto et al 8…”
Section: Editorial: Which Factors Influence Hbsag Levels In Hbv-infecmentioning
confidence: 99%
“…Hepatitis B virus, a common infectious disease worldwide, had a characteristic of high morbidity and mortality. According to the reports, about 240 million people worldwide were chronically infected with HBV (Cavallone et al, 2020;Li et al, 2020c). More than 700,000 people died from HBV-associated diseases each year (Bhuiyan et al, 2020).…”
Section: Interleukin-35 and Hepatitis B Virusmentioning
confidence: 99%